Thymol and carvacrol supplementation in poultry health and performance - Majid Gholami‐Ahangaran; Asiye Ahmadi‐Dastgerdi; Shahrzad Azizi; Asal Basiratpour; Maryam Zokaei; Masoud Derakhshan (Veterinary Medicine and Science, 2022)
Abstract Background Thymol and carvacrol as natural essential oils and phenol compounds are components derived from some medicinal plants, such as thyme and oregano species. Objectives The increasing demands in organic and healthy meat and egg consumption in human society have made it necessary to consider alternative natural compounds for the replacement of chemical compounds in poultry production. The chemical compounds can remain in meat and eggs and cause complications in human health. Therefore, these natural compounds can be fed with a higher safety in poultry production with specific effects. In this regard, the role of thymol and carvacrol as natural compounds in the poultry production has been discussed in the review. Methods In this study, by searching for keywords related to thymol and carvacrol in poultry production in Google Scholar database, the articles related to different aspects of the biological effects of these two phytogenes in poultry production were selected and analyzed. Results A review of previous studies has shown that thymol and carvacrol possess a wide range of biological activities, including antibacterial, antiviral, antioxidant, anti‐inflammatory, modulating of immunity response and regulating of the gut microbial population. Also, in meat type chickens can promote growth and influence feed utilization. The beneficial effect of this compound was evaluated in hepatic toxicity and demonstrated as a hepatoprotective compound in chickens. Furthermore, these compounds can affect the behavior of layers and influence egg composition, eggshell thickness, and the sensory quality of eggs. Conclusion It seems that with the increasing demand for healthy protein products, these compounds can be used to improve performance as a substitute alternative for chemical compounds in healthy poultry farms.